O MARKETING PESSOAL NO SETOR VAREJISTA: UM ESTUDO COM GESTORES NO MUNICÍPIO DE SANTA ROSA - Wagner, Wander G.; Graef, Nelinho D.; Zamberlan, Luciano; Sparemberger, Ariosto; Martinelli, Marlen; Martini, Rodrigo N.; Oliveira, Charlene; Büttenbender, Pedro L. (Salão do Conhecimento, 2013)
Resumo